Resurgent Turkey: the Turkish model and the Arab Spring - Irena Rajchinovska Pandeva (Iustinianus Primus Law Faculty, 2013)
The Arab Spring has brought significant change and turbulence in the Middle East region. Concerning the developments and future prospects, the debate on the Turkish model has intensified once again. For over six decades, Turkey has a democratic society, democratic elections, plural political system, institutions based on democratic accountability and a long-standing tradition of secular government. The Turkish model is probably the most relevant one to the wider region, because it incorporates successfully the principal elements of both worlds: East and West. Although labeled as ‘work in progress’, it is the finest know-how and the best practice available to the awoken peoples of the Arab spring. Its history offers quite a few lessons for those interested in implementing the ideas and institutions from the West into the East and it suggests that this objective can be achieved, although it takes a long time. Moreover, this is why after the Arab spring, the Turkish model became vigorously operational.
Keywords: Turkey, Arab Spring, reform